Impact of the activities of governed-sponsored enterprises on the financial policy of the state: case of Ukraine - Tkachuk, I; Zhavoronok, A; Kobelia, M (European Journal of Accounting, Finance & Business, 2021)
Within the article, the parameters of determining financial impact of governed-sponsored enterprises on the financial policy of Ukraine are researched. After the analysis it is substantiated that financial impact of governed-sponsored enterprises on the financial policy of Ukraine is primarily implemented through the amount of taxes, fees and other mandatory payments paid by public sector enterprises to the State Budget (income tax of state-owned enterprises, part of net profits withdrawn from the budget, rent payments, payment of other taxes and fees). In first turn, it affects the fiscal policy, which is a key component of the Ukraine’s fiscal policy. In addition, the parameters of profit distribution of governed-sponsored enterprises are key characteristics of the dividend policy. Investment decisions made by management of governed-sponsored enterprises largely determine the investment policy in certain industries in which these enterprises are dominant. Given a small volume of foreign exchange transactions in the official foreign exchange market of Ukraine, state-owned enterprises that buy (sell) foreign currency have a significant impact on the exchange rate, which is an important parameter of the monetary policy.
Keywords: state; enterprise; public sector of the economy; financial policy.